Fabrication of pH/Redox Dual-Responsive Mixed Polyprodrug Micelles for Improving Cancer Chemotherapy - Luo, Ji; Zhang, Shuguang; Zhu, Peiyao; Liu, Wenke; Du, Jiang (Frontiers in Pharmacology, 2022)
In this work, we prepared pH/redox dual-responsive mixed polyprodrug micelles (MPPMs) which were co-assembled from two polyprodrugs poly(ethylene glycol) methyl ether-b-poly(β-amino esters) conjugated with doxorubicin (DOX) via redox-sensitive disulfide bonds (mPEG-b-PAE-ss-DOX) and poly(ethylene glycol) methyl ether-b-poly (β-amino esters) conjugated with DOX via pH-sensitive cis-aconityl bonds (mPEG-b-PAE-cis-DOX) for effective anticancer drug delivery with enhanced therapeutic efficacy. The particle size of MPPMs was about 125 nm with low polydispersity index, indicating the reasonable size and uniformly dispersed. The particle size, zeta-potential, and critical micelle concentration (CMC) of MPPMs at different mass ratios of two kinds of polyprodrugs were dependent on pH value and glutathione (GSH) level, suggesting the pH and redox-responsiveness. The drug release profiles in vitro of MPPMs at different conditions were further studied, showing the pH- and redox-triggered drug release mechanism. Confocal microscopy study demonstrated that MPPMs can effectively deliver doxorubicin molecules into MDA-MB-231 cells. Cytotoxicity assay in vitro proved that MPPMs possessed high toxic effect against tumor cells including A549 and MDA-MB-231. The results of In vivo experiments demonstrated that MPPMs were able to effectively inhibit the tumor growth with reduced side-effect, leading to enhanced survival rate of tumor-bearing mice. Taken together, these findings revealed that this pH/redox dual-responsive MPPMs could be a potential nanomedicine for cancer chemotherapy. Furthermore, it could be a straightforward way to fabricate the multifunctional system basing on single stimuli-responsive polyprodrugs.